TEKNIK PEMBENIHAN IKAN MAS(Cyprinus carpio,L) di BALAI BENIH IKAN (BBI) TENGGARANG BONDOWOSO - Ismail Ismail; Ach. Khumaidi (Faculty of Science and Technology University Ibrahimy, 2016)
Carp (Cyprinus carpio, L.) is a species of freshwater fish that has long been cultivated and domesticated well in the world. In China, farmers have cultivated around 4,000 years ago, while in Europe several hundred years ago. Some fish varieties and subvarietas Mas Southeast Asia has been widely cultivated as a food fish and ornamental fish. C. carpio spawn at 22.00 until dawn marked with fish activity male chasing the female parent. When it rains fish usually spawn faster. Mas process of spawning fish is the female parent will release eggs while keeping up with the male parent where the male parent while it also spray his sperm on the egg. It is important also pursued when the activity takes place the water continues to flow to supply oxygen dissolved in the fish kolam.Pembenihan Mas can be done in the traditional way, semi-intensive and intensive. The mortality rate in the hatchery can reach 10-20%, it is because the eggs did not hatch due to the muddy water that covered the surface of the egg. Consequently affect hatching, each pool must be no drain water income and expenditure.